Sand! - Llewellyn, Claire; Beard, Lauren (Wayland London, 2010)
Fun at the Beach is a series of four books at Pink Band 1A of the Start Reading programme. The family are on a trip to the beach. They play in the sea, fish in the rock pools and get covered in sand!